Say-Hey and the Babe : two mostly-true baseball stories - Waldman, Neil (Holiday House, 2006)
Presents two interrelated stories, based on fact, about the 1927 New York Yankees, the 1951 New York Giants, and a stickball team from the Bronx. Sidebars explain baseball terms and events of the time periods, players' nicknames, and stickball lore.